2014
DOI: 10.1182/blood-2014-04-560813
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease increases high mobility group box 1: a novel mechanism of inflammation

Abstract: High mobility group box 1 (HMGB1) is a chromatin-binding protein that maintains DNA structure. On cellular activation or injury, HMGB1 is released from activated immune cells or necrotic tissues and acts as a damage-associated molecular pattern to activate Toll-like receptor 4 (TLR4). Little is known concerning HMGB1 release and TLR4 activity and their role in the pathology of inflammation of sickle cell disease (SCD). Circulating HMGB1 levels were increased in both humans and mice with SCD compared with contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 32 publications
2
64
0
Order By: Relevance
“…Histological analyses of liver and lung tissues revealed no evidence of fibrin thrombi in H/R-treated SS and SSCKO mice (Figure 5A). The absence of visible thrombi is consistent with previous studies in Berkeley sickle mice, which found evidence of hepatic ischemia but no thrombosis [41]. A number of studies have indicated the presence of PAH in Berkeley sickle mice using parameters such as elevated pulmonary artery pressure [42] and left and right ventricular end-diastole volumes [11].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Histological analyses of liver and lung tissues revealed no evidence of fibrin thrombi in H/R-treated SS and SSCKO mice (Figure 5A). The absence of visible thrombi is consistent with previous studies in Berkeley sickle mice, which found evidence of hepatic ischemia but no thrombosis [41]. A number of studies have indicated the presence of PAH in Berkeley sickle mice using parameters such as elevated pulmonary artery pressure [42] and left and right ventricular end-diastole volumes [11].…”
Section: Resultssupporting
confidence: 87%
“…Consistent with previous findings in the Berkeley sickle mice [13, 41], we found little evidence for hepatic thrombi formation in Townes SS and SSCKO mice despite H/R-induced platelet hyperactivity. In contrast to previous studies in the Berkeley mice [42], we did not find evidence of pulmonary arterial hypertension (PAH), as measured by elevated right ventricular systolic pressure (RVSP) in the Townes sickle mice.…”
Section: Discussionsupporting
confidence: 92%
“…HMGB1 accounts for the majority of sickle cell plasma-induced TLR4 activity both in vitro and in vivo. 101 …”
mentioning
confidence: 99%
“…Secretion of HMGB1 is controlled by the NLRP3 inflammasome in monocytes/macrophages (Willingham et al , ). Plasma derived from SCD patients at baseline and plasma from SCD mice induced TLR4 activity in a TLR4 reporter cell line in an HMGB1‐dependent manner, further increased when plasma from SCD crisis patients was used (Xu et al , ). Other studies have shown that HMGB1 promotes inflammation in human microvascular endothelial cells (Fiuza et al , ) and promotes thickening of the pulmonary artery wall in a rat model of pulmonary arterial hypertension (Sadamura‐Takenaka et al , ).…”
Section: Pattern Recognition Receptor Signaling In Plateletsmentioning
confidence: 99%
“…The DNA‐binding protein high‐mobility group box 1 (HMGB1) is a non‐erythrocyte DAMP associated with haemolysis and abnormal coagulation, including sepsis (Wang et al , ), disseminated intravascular coagulation (DIC) (Hatada et al , ), trauma (Levy et al , ), HUS (Lee et al , ) and SCD (Xu et al , ). HMGB1 plasma levels are elevated in SCD patients at baseline and further increased during acute sickling events (Xu et al , ). HMGB1 induces thrombosis and inflammation when exported to the cell surface or released into the extracellular space by stressed or dying cells and activated platelets (Rouhiainen et al , ; Andersson & Tracey, ; Maugeri et al , ; Gawaz & Vogel, ; Vogel et al , , ,b, ).…”
mentioning
confidence: 99%